Sorghum and millets diseases a second world review - De Milliano, W.A.J.; Frederiksen, R.A.; Bengston, G.D. (Patancheru (India), 1992)
Sumarios (Es, En, Fr)
Ilus.; 47 ref.
Keywords: SORGHUM; MIJOS; ENFERMEDADES DE LAS PLANTAS; INVESTIGACION